2007
DOI: 10.1152/ajpgi.00323.2007
|View full text |Cite
|
Sign up to set email alerts
|

CD4 T cells activated in the mesenteric lymph node mediate gastrointestinal food allergy in mice

Abstract: A localized Th2 milieu has been observed in the intestine of subjects with food allergic disorders; however, the role of T cells in the pathophysiology of these disorders remains poorly understood. Our aim was to examine sites of T cell activation in response to food challenge, identify potential factors responsible for T cell recruitment to the gut, and determine the role of T cells in disease. BALB/c mice were systemically sensitized to ovalbumin (OVA) and repeatedly fed with OVA to induce allergic diarrhea.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 36 publications
5
76
1
1
Order By: Relevance
“…Eosinophils constitute another principal effector cell type that induces gastrointestinal tissue injury and disease pathogenesis through the release of various toxic granule proteins, lipid mediators and proinflammatory cytokines [34] . Compared with other allergy models, the accumulation of inflammatory cells in these mice does not require repetitive intragastric challenge [15,35] . The gastrointestinal tract mucus layer is the front line of innate host defense [36] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils constitute another principal effector cell type that induces gastrointestinal tissue injury and disease pathogenesis through the release of various toxic granule proteins, lipid mediators and proinflammatory cytokines [34] . Compared with other allergy models, the accumulation of inflammatory cells in these mice does not require repetitive intragastric challenge [15,35] . The gastrointestinal tract mucus layer is the front line of innate host defense [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [16] reported a 20% incidence of diarrhea after one challenge. Moreover, Knight et al [35] reported an incidence of 100% after a single dose challenge in their OVA murine model, while lower allergen doses reduced the incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Food allergies have been noted in 13-25% with specific positive IgE due to certain foods in 40% of adults [27,28]. These allergies are thought to be mediated by activated CD4 + T cells, found in the mesenteric lymph nodes [29].…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%
“…Moreover, the allergic response is characterized by Th2 proliferation, and Th2-associated cytokines and chemokines can be found in the serum of allergic patients. In a model of food allergy in mice, the receptor CCR8 and the ligands of CCR4, CCL17, and CCL22 were overexpressed in the intestine (70). Once again, the receptor CX3CR1 is also involved in food allergies.…”
Section: Chemokine Receptors In Food Allergymentioning
confidence: 97%